2013
DOI: 10.1371/journal.pone.0071100
|View full text |Cite
|
Sign up to set email alerts
|

Popeye Domain Containing 1 (Popdc1/Bves) Is a Caveolae-Associated Protein Involved in Ischemia Tolerance

Abstract: Popeye domain containing1 (Popdc1), also named Bves, is an evolutionary conserved membrane protein. Despite its high expression level in the heart little is known about its membrane localization and cardiac functions. The study examined the hypothesis that Popdc1 might be associated with the caveolae and play a role in myocardial ischemia tolerance. To address these issues, we analyzed hearts and cardiomyocytes of wild type and Popdc1-null mice. Immunoconfocal microscopy revealed co-localization of Popdc1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(100 citation statements)
references
References 57 publications
5
95
0
Order By: Relevance
“…We studied the expression of proteins involved in membrane stability and repair in PTI-1 and PTIII-2 in comparison with 2 controls (Supplemental Figures 5-9). We previously reported protein-protein interaction of POPDC1 with CAV3 (12). However, the membrane presence of CAV3 was not altered in the patients' POPDC2 were prominently expressed in the sarcolemma ( Figure 2, A, B, E, and Figure 3, A, B, and E).…”
Section: Popdc1 Is a Disease-causing Gene Associated With Cardiac Dismentioning
confidence: 75%
See 2 more Smart Citations
“…We studied the expression of proteins involved in membrane stability and repair in PTI-1 and PTIII-2 in comparison with 2 controls (Supplemental Figures 5-9). We previously reported protein-protein interaction of POPDC1 with CAV3 (12). However, the membrane presence of CAV3 was not altered in the patients' POPDC2 were prominently expressed in the sarcolemma ( Figure 2, A, B, E, and Figure 3, A, B, and E).…”
Section: Popdc1 Is a Disease-causing Gene Associated With Cardiac Dismentioning
confidence: 75%
“…The Popdc1 null mutant in mice displays a retardation of muscle regeneration (13). Moreover, an impaired recovery from cardiac ischemia and an increase in infarct size have been described in the Popdc1 null mutant (12). Both Popdc1 and Popdc2 null mutants display a stress-induced sinus node bradycardia, which develops in an age-dependent manner (10,14).…”
Section: Popdc1 S201fmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was reported that BVES plays a regulatory role in cardiac pacemaking through binding of cAMP and interacting with potassium channel TREK-1 41 . Further, BVES interacts with CAV3, a caveolin expressed in the muscle tissue, and cardiac myocytes in Bves −/− mice have altered calveolar number and size 42 . Thus, BVES, through scaffolding with protein complexes, regulates a wide variety of basic, yet essential, cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the human heart, Popdc1/Bves is markedly reduced during end stage heart failure and mutated Popdc1/Bves has been identified in patients born with Fallot's tetralogy and with muscular dystrophy [Gingold‐Belfer et al, ; Wu et al, ; Schindler et al, ], suggesting its involvement in heart pathology and morphogenesis. The ability of Popdc1/Bves to interact with ion channels and bind cAMP [Froese et al, ], as well as the presence of Popdc1/Bves in the caveolae and its interaction with caveolin3 [Alcalay et al, ], provide a partial description of mechanisms underlying the functional deficits reported in hearts lacking Popdc1/Bves. In addition, the downregulation of Popdc1/Bves expression due to promoter hypermethylation has been associated with tumorigenic transformation in humans that correlated with increased cell motility and invasiveness [Kim et al, ; Williams et al, ; Han et al, ].…”
mentioning
confidence: 99%